Mini-Factor H Modulates Complement-Dependent IL-6 and IL-10 Release in an Immune Cell Culture (PBMC) Model: Potential Benefits Against Cytokine Storm - Kozma, Gergely Tibor; Mészáros, Tamás; Bakos, Tamás; Hennies, Mark; Bencze, Dániel; Uzonyi, Barbara; Győrffy, Balázs; Cedrone, Edward; Dobrovolskaia, Marina A.; Józsi, Mihály; Szebeni, János (Frontiers in Immunology, 2021)
Cytokine storm (CS), an excessive release of proinflammatory cytokines upon overactivation of the innate immune system, came recently to the focus of interest because of its role in the life-threatening consequences of certain immune therapies and viral diseases, including CAR-T cell therapy and Covid-19. Because complement activation with subsequent anaphylatoxin release is in the core of innate immune stimulation, studying the relationship between complement activation and cytokine release in an in vitro CS model holds promise to better understand CS and identify new therapies against it. We used peripheral blood mononuclear cells (PBMCs) cultured in the presence of autologous serum to test the impact of complement activation and inhibition on cytokine release, testing the effects of liposomal amphotericin B (AmBisome), zymosan and bacterial lipopolysaccharide (LPS) as immune activators and heat inactivation of serum, EDTA and mini-factor H (mfH) as complement inhibitors. These activators induced significant rises of complement activation markers C3a, C4a, C5a, Ba, Bb, and sC5b-9 at 45 min of incubation, with or without 5- to 2,000-fold rises of IL-1α, IL-1β, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, IL-13 and TNFα at 6 and 18 h later. Inhibition of complement activation by the mentioned three methods had differential inhibition, or even stimulation of certain cytokines, among which effects a limited suppressive effect of mfH on IL-6 secretion and significant stimulation of IL-10 implies anti-CS and anti-inflammatory impacts. These findings suggest the utility of the model for in vitro studies on CS, and the potential clinical use of mfH against CS.